2013
DOI: 10.1089/omi.2012.0124
|View full text |Cite
|
Sign up to set email alerts
|

Gene Panel Model Predictive of Outcome in Patients with Prostate Cancer

Abstract: In men at high risk for prostate cancer, established clinical and pathological parameters provide only limited prognostic information. Here we analyzed a French cohort of 103 prostate cancer patients and developed a gene panel model predictive of outcome in this group of patients. The model comprised of a 15-gene TaqMan Low-Density Array (TLDA) card, with gene expressions compared to a standardized reference. The RQ value for each gene was calculated, and a scoring system was developed. Summing all the binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…This result indicated that, the estrogens via their ER alpha might inhibit growth of prostate cancer cells. Previously, we demonstrated that patients with Gleason score at 6 revealed no significant difference in the expression of ER alpha compared with the normal tissues [ 31 ]. However in this study, a positive correlation was observed between decreased ER alpha expression and tumor aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that, the estrogens via their ER alpha might inhibit growth of prostate cancer cells. Previously, we demonstrated that patients with Gleason score at 6 revealed no significant difference in the expression of ER alpha compared with the normal tissues [ 31 ]. However in this study, a positive correlation was observed between decreased ER alpha expression and tumor aggressiveness.…”
Section: Discussionmentioning
confidence: 99%